Agroecology providing access to markets for small rural producers: the case of Centro Sabiá (Research, Society and Development, 2021)
When questioning one of the greatest difficulties faced by the rural population in the Brazilian semi-arid region, it can be said that the biggest challenge concerns the prolonged periods of water scarcity in the region, the aridity of the climate and the presence of soils poor in organic matter, challenges these, which to be faced, lack alternatives associated with sustainable forms of management of natural resources. In this context, agroecological production incurs a direct relationship with the practices carried out by the rural population whose main occupation of the workforce is agriculture, while providing conditions for the small rural producer to have access to local markets and, from there, achieve an improvement in quality of life. In the face of such issues, the present study aimed to carry out a study on projects of an environmental nature and of a sustainable character carried out in rural areas, in the Sertão do Pajeú, and which are guided by agro-ecological practices, aiming to verify how these projects have transformed social contexts in the countryside. To this end, the present work proceeded with the identification of a rich and distinct set of projects that operate in the segment of agroecology. A number of aspects were identified that are responsible for enhancing the transition from the traditional model of agriculture to the model of agroecological production, which has enhanced the access of small rural producers to local markets and the generation of income, thus improving the quality of their lives.